Speak Our Minds: Using Task-Based Learning to Enhance the Development of Oral Production in Fifth Graders (2022)
ABSTRACT: This action research aims to describe how task-based learning implementation enhances the development of oral production in a fifth graders group. The participants were 40 students from La Salle Campoamor, a public school in Medellín - Colombia. The actions/tasks implemented during the project were focused on promoting language interactions among the students. Some tasks implemented were planning a birthday, talking about your classmate, and guessing who is. The data collection instrument included journals, a focus group, and an interview with the cooperating teacher. The findings of this research demonstrated that Task-based learning implementation helps students to enhance oral production abilities,and it also helps to encourage students' participation and engagement.